52nd Electronic Components and Technology Conference 2002. (Cat. No.02CH37345)
DOI: 10.1109/ectc.2002.1008260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electromigration on intermetallic compound formation in Pb-free solder-Cu interfaces

Abstract: The polarity effect of electromigration on intermetallic compound (IMC) formation at the cathode and the anode in solder lines has been investigated. The lines were formed by flowing molten lead-free solder SnAg3.8Cuo.7 into V-grooves etched on (001) silicon wafers, and two copper wires were used as electrodes. The V-groove solder line samples, with width of about lOOpm and length of 600-800p1, were used to study the changes in thickness and morphology of IMC forming at the cathode and the anode in the SnAg3.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Gan and Tu reported that Cu-Sn IMC growth was enhanced at the anode side and inhibited at the cathode side, as a result of electron flow in the Cu/Sn-3.8Ag-0.7Cu/Cu system in the model solder strip form [21]. Ebersberger et al reported that Cu-Sn IMC growth was enhanced through the entire joint of the thin-Ni/Sn-Ag/ Cu system [31].…”
Section: Polarity Effect On Imc Growthmentioning
confidence: 98%
See 1 more Smart Citation
“…Gan and Tu reported that Cu-Sn IMC growth was enhanced at the anode side and inhibited at the cathode side, as a result of electron flow in the Cu/Sn-3.8Ag-0.7Cu/Cu system in the model solder strip form [21]. Ebersberger et al reported that Cu-Sn IMC growth was enhanced through the entire joint of the thin-Ni/Sn-Ag/ Cu system [31].…”
Section: Polarity Effect On Imc Growthmentioning
confidence: 98%
“…Tu and co-workers reported on the electromigration of Sn-37Pb, Sn-3.5Ag and Sn-3.8Ag-0.7Cu [19][20][21][22] and disclosed the existence of a polarity effect influencing IMC growth at the solder/ Cu interface. Chen and co-workers reported on the IMC formation in several diffusion couples such as Al/Ni, Sn/Cu, Sn/Ni, Sn/Ag, Sn-0.7Cu/Ni and Sn-3.5Ag/Ni, using current density magnitudes of 0.5 and 1 kA/cm 2 [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…BSE image and phase map determined from EPMA X-ray map of Sn57Bi bump on Ni/Au pad after current stressed by 4.0×10 4 A/cm 2 at 125 degree C for 10 % resistivity changes is shown in .…”
Section: Electro-migration Phenomenon Of Sn-bi Eutectic Solder Usingmentioning
confidence: 99%
“…The critical current density at flip chip joint is lower than that in LSI pattern which is generally recognized as a case of electro-migration failure. The current density at the micro solder joint is expected to be in the order of 1x10 4 A/cm 2 2-4) .…”
Section: Introductionmentioning
confidence: 99%
“…According to the work in [10] and JEDEC standard JEP154, both temperature and current density were responsible for the degradation of FC solder bumps. Additionally, the environmental temperature of 150°C was suggested as a critical upper limit for EM tests [6,11], and the current density of 1 Â 10 4 A/cm 2 a stressing threshold [12]. From the survey of literature [5,6,[11][12][13], most EM tests were generally addressed one as main condition, i.e., either current density or temperature, and each condition resulted in a unique failure mode.…”
Section: Introductionmentioning
confidence: 99%